Laser Adjustment Using Actuators - Hagenah, Hinnerk; Geiger, Manfred (60 Excellent Inventions in Metal Forming, 2015)
After the identification and classification of laser forming mechanism the potentials of this technology in the field of adjustment was discovered. In order to use the possibilities in the field of micro systems technology the idea of specifically designed, task specific actuators was born and researched. The detected challenge of actuator design has been addressed with suitable algorithms models. The paper gives an overview of the possibilities and explains how the design challenge has been overcome.
LFT Import::2019-08-05 (2094)